Understanding the Basic Concepts and Scope of Excellent Service in Professional Practice at the UNESA Global Engagement Directorate (International Journal of Economics and Management Research, 2026)
Understanding the basic concepts and scope of excellent service is the main foundation in building a culture of service excellence in higher education. The purpose of this chapter is to describe the professional practices of the UNESA Global Engagement (UGE) Directorate in implementing the values of service excellence in a tangible and sustainable manner. The conceptual basis is rooted in the Grand Theory of Parasuraman, Zeithaml, and Berry (1988) on Service Quality (SERVQUAL), which emphasizes five main dimensions of service quality, namely tangibles, reliability, responsiveness, assurance, and empathy. This theory serves as a foundation for understanding the meaning of service, the definition of excellent service, and the application of its basic concepts in the context of academic and international services in higher education. As a result, service practices at the UGE Directorate show that service excellence is not only realized through administrative systems and procedures, but also through the internalization of the values of professionalism, empathy, and commitment to the satisfaction of global partners. The implementation of a responsive, solution-oriented, and real-time cooperation information system (SIMKERMA) is a tangible representation of the integration of digital efficiency and a human touch in university public services. The recommendations from this chapter emphasize the importance of strengthening human resource capacity that is adaptive to global dynamics, optimizing digital technology to accelerate service processes, and establishing a structured, measurable, and sustainable ecosystem of excellent service to strengthen the university's position as an internationally competitive institution.